Detection of Simultaneous Faults Using State Observer Methodology - Araújo, Camilo Rocha [UNESP]; de Melo, Gilberto Pechoto [UNESP] (Springer Nature, 2021)
Due to the big interest of industries in predictive maintenance, the development of techniques to diagnose failures has been gradually acquiring a relevant role in the current industrial scenario. For this reason, this paper aims to evaluate a fault diagnosis methodology based on the state observer theory, considering simultaneous failures. In order to validate this methodology, a system of vibrating tables was built to perform experimental tests, which consist of inputting two failure modes in a mechanical structure: mass loss and stiffness loss. The system is, then, excited by a shaker, and its response is measured. Applying the measured signals (the input and output) in the mathematical system model, the state observer methodology was, thus, executed to estimate the observable system states. The estimated state corresponding to the measured state is compared to the measured signal, resulting in a fault metric that can be used for failures characterization.
Keywords: Simultaneous failures; State observer methodology